The invisible teacher: The teacher envisaged in the Curriculum and Assessment Policy Statement (CAPS) English First Additional Language (EFAL) Further Education and Training (FET) Phase - Dowejko, Diane Agnieszka (Rhodes University, Faculty of Humanities, Department of Linguistics and Applied Language Studies)
Educational policy documents, which are intended to enlighten teachers about what they should teach and how they should assess learners, contain both language and knowledge. How this knowledge is construed through language may reveal the kind of teacher envisaged by the document, and the assumptions made regarding the dispositions of these educators. There is a plethora of research on the relationship between the Curriculum and Assessment Policy Statement for English First Additional Language in the Further Education and Training Phase (CAPS-EFAL) and its impact on the learner in the classroom, but little evidence of research related to how curriculum documents envisage the teacher, and linguistic research pertaining to CAPS-EFAL. This research aims to use linguistic analysis to discover how the teacher is envisaged in this document, while speaking to the broader subject of the relationship between teacher and curriculum policy. This study adopts a framework which inspects this language using Systemic Functional Linguistics to analyse language in relation to its functions in social contexts, and the instructional knowledge built in CAPS-EFAL through applying elements of Legitimation Code Theory, analysing processes of knowledge production and recontextualisation. An investigation of the language revealed assumptions that the envisaged teacher is one who is already highly trained in aspects of language teaching and classroom methodology and pedagogy. While the analysis also revealed a high level of guidance for the teacher, there was a strong focus on the knowledge within the curriculum, and several assumptions made regarding the teacher's prior knowledge before encountering or utilising the document. The analysis also revealed that CAPS-EFAL acknowledges that the teacher requires a sound knowledge of technical terminology related to language teaching, as well as general classroom pedagogies and routines. In addition, the document assumes that the disposition of the teacher is one who can make decisions without the need for absolute confirmation or authority from curriculum documentation. Overall, the analysis revealed an élite code in terms of Specialization; CAPS-EFAL is therefore based on the legitimacy of both specialised knowledge and the disposition of the teacher.
Keywords: Educational sociology -- South Africa; Systemic functional linguistics; Curriculum-based assessment -- South Africa; Linguistic analysis (Linguistics); Educational evaluation -- South Africa